2012
DOI: 10.3892/ol.2012.570
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating serum pro-prostate-specific antigen in patients with rising PSA following radical prostatectomy

Abstract: Abstract. [-2]pro-prostate-specific antigen (2pPSA), a proform of PSA, is a new marker in patients at risk of prostate cancer. We explored the potential role of 2pPSA in the identification of patients with metastatic progression following radical prostatectomy for prostate cancer. Seventy-six patients with biochemical (PSA) recurrence following radical prostatectomy were studied retrospectively. Diagnostic imaging performed at the time of biochemical recurrence confirmed metastatic disease in 31 of the 76 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Sottile investigated the role of [−2]proPSA in the identification of patients with metastatic progression after RP [ 32 ]. In this study, 76 patients with BCR were retrospectively studied; the imaging performed at BCR time confirmed metastatic disease in 31 out of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sottile investigated the role of [−2]proPSA in the identification of patients with metastatic progression after RP [ 32 ]. In this study, 76 patients with BCR were retrospectively studied; the imaging performed at BCR time confirmed metastatic disease in 31 out of them.…”
Section: Discussionmentioning
confidence: 99%
“…Median PSA, free PSA (fPSA), %fPSA, [−2]proPSA and PHI were compared between metastatic and non-metastatic patients; [−2]proPSA was a statistically significant predictor of imaging-proven metastatic PCa. However, [−2]proPSA was assessed only at BCR time, so no information may be derived on its potential role, in predicting subsequent clinical progression, when measured at BCR time [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tosoian et al [ 10 ] found an association between baseline and longitudinal PHI, but not PCA3 [ 11 ] values and reclassification during active surveillance. Sottile et al [ 12 ] demonstrated significantly higher p2PSA and PHI levels in men with metastatic disease as compared to those without clinical metastasis. Collectively, PHI and/or PCA3 improve the selection of eligible patients for AS and decision curve analysis demonstrated that PHI outperforms PCA3 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%